Odpowiedzi

2009-10-27T16:08:39+01:00
(3√5-2)(2√3+3) = 6√15+9√3-4√3-6 = 6√15+5√3-6

-2√8-3√18+2√2 = -2*2√2-3*3√2+2√2 = -4√2-9√2+2√2 =-11√2
2*2√2, bo 4*2=8, a √4=2
3*3√2, bo 9*2=18, a √9=3

(√3-2)³= 3√3-18+12√3+8=15√3-10
wzór skróconego mnożenia (a-b)³=a³-3a²b+3ab²+b³

√49*(-2)³-³√8:(-4)⁰ =7*(-8)-2:1= -56-2=-58
jakakolwiek liczba podniesiona do potęgi 0 daje 1
2009-10-27T16:09:56+01:00
1.(3/5-2)+(2/3+3)=-2,6+3,6=1
2.-2/8-3/18+2/2=-4-6+1=1
3.(/3-2)³=/3
4.49*(-2)³-³√8:(-4)=-98-(-2)=-100
Najlepsza Odpowiedź!
2009-10-27T16:15:38+01:00
(3√5-2)(2√3+3)=3√5 *2√3+3√5*3-2*2√3-2*3=6√15+9√5-4√3-6
-2√8-3√18+2√2=-2√2*4-3√9*2+2√2=-4√2-9√2+2√2=-11√2
(√3-2)3=√33-3*√32*2+3*√3*22-23=3√3-18+12√3-8=15√3-26
√49*(-2)3-3√8:(-4)0= 7*(-8)-2:(-1)=-56-2=-58